Usability Evaluation of Educational Games: An Analysis of Culture as a Factor Affecting Children’s Educational Attainment - Marwan Alshar’e; Ali Albadi; Malik Jawarneh; Noman Tahir; Marya Al Amri (Advances in Human-Computer Interaction)
Educational games have been employed among Omani schools but those used by local Omani schools were imported and were mostly designed based on western contexts. For Omani children, these games may be culturally inappropriate and difficult to comprehend and follow, impeding children’s learning. Three questionnaires and one observational checklist were used to gather data from 40 respondents (observers). SPSS was used in data analysis. Through experiments, the behavior of Omani students towards the use of imported educational games was examined. Five main factors, namely, efficiency, learnability, memorability, errors, and satisfaction, of educational games for a target user were measured using Hybrid User Evaluation Methodology for Remote Evaluation (HUEMRE), Training Framework for Untrained Observer (TFUO), and Framework on Educational Games Behavior Intention (EGsBI), which are specifically designed frameworks for this purpose. The results of this study explained that the Omani children are facing difficulties in using the imported educational games; furthermore, this study proves that culture, language, animation, and interaction are contributing heavily to benefiting from educational games, and, therefore, these factors shall be highly considered in the process of educational games design to facilitate and ensure children learning; furthermore, the findings of this study enrich the comprehension of how the specified factors positively affect behavioral intention of Omani students in the use of educational games and in improving the behavior intention level of these students.